A new osmiine bee with a spectacular geographic disjunction: Hoplitis (Hoplitis) onosmaevae sp. nov. (Hymenoptera, Anthophila, Megachilidae) - Matthieu Aubert; Andreas Müller; Christophe Praz (Alpine Entomology, 2024)
A new osmiine bee species, Hoplitis (Hoplitis) onosmaevae sp. nov. (Megachilidae), is described. So far, this species is exclusively known from the Mercantour National Park in the southwestern French Alps and from mountainous ranges in Turkey and northern Iraq, two areas separated by at least 2000 km. Phylogenetic analyses based on mitochondrial and nuclear genes revealed that H. onosmaevae is closely related to H. adunca (Panzer, 1798), H. benoisti (Alfken, 1935) and H. manicata (Morice, 1901). Hoplitis onosmaevae is presumably narrowly oligolectic and harvests pollen only on flowers of Onosma L. (Boraginaceae). It has a particularly long proboscis, which is probably an adaptation to collect nectar from the long-tubed flowers of this plant genus. The females collect pollen by buzzing the Onosma flowers, a rare behavior in megachilid bees. The species nests in insect burrows in dead wood, similar to H. adunca and H. manicata but unlike other closely related representatives of the subgenus Hoplitis, suggesting a single origin of nesting in dead wood and hollow stems in this lineage. In France, H. onosmaevae inhabits alpine steppe-like habitats close to forests and appears to be extremely local, since only two populations are currently known. The conservation status of this extremely rare bee species in Europe is discussed.